2020
DOI: 10.1021/acschembio.9b01044
|View full text |Cite
|
Sign up to set email alerts
|

Selective Fluorogenic β-Glucocerebrosidase Substrates for Convenient Analysis of Enzyme Activity in Cell and Tissue Homogenates

Abstract: Within mammals, there are often several functionally related glycoside hydrolases, which makes monitoring their activities problematic. This problem is particularly acute for the enzyme β-glucocerebrosidase (GCase), the malfunction of which is a key driver of Gaucher's disease (GD) and a major risk factor for Parkinson's disease (PD). Humans harbor two other functionally related β-glucosidases known as GBA2 and GBA3, and the currently used fluorogenic substrates are not selective, which has driven the use of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The flexibility of GBA for substrates with a modification at the glucose-C6 is also reflected by its selective reactivity with O8-modified cyclophellitol-based inhibitors and ABPs and with those of glucose-C6 modified substrates. [33][34][35][36] In the study we report here, we examined whether xyloseconfigured cyclophellitol and cyclophellitol aziridines can react with GBA, GBA2 and/or GBA3 in vitro and in vivo, by applying activity-based protein profiling (ABPP) and fluorogenic readouts (Figure 2). These studies reveal that xylo-cyclophellitol is a highly selective GBA inhibitor, more potent and more selective than the widely applied GBA inhibitor, CBE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flexibility of GBA for substrates with a modification at the glucose-C6 is also reflected by its selective reactivity with O8-modified cyclophellitol-based inhibitors and ABPs and with those of glucose-C6 modified substrates. [33][34][35][36] In the study we report here, we examined whether xyloseconfigured cyclophellitol and cyclophellitol aziridines can react with GBA, GBA2 and/or GBA3 in vitro and in vivo, by applying activity-based protein profiling (ABPP) and fluorogenic readouts (Figure 2). These studies reveal that xylo-cyclophellitol is a highly selective GBA inhibitor, more potent and more selective than the widely applied GBA inhibitor, CBE.…”
Section: Introductionmentioning
confidence: 99%
“…The flexibility of GBA for substrates with a modification at the glucose‐C6 is also reflected by its selective reactivity with O8‐modified cyclophellitol‐based inhibitors and ABPs and with those of glucose‐C6 modified substrates. [ 33 , 34 , 35 , 36 ]…”
Section: Introductionmentioning
confidence: 99%
“…To that end, we treated SK-N-SH cells with AT3375, a highly potent and selective GCase inhibitor. [44] Cells were then imaged before or after fixation with PFA. Notably, no signal was observed within inhibitor treated cells, whether live or fixed, which demonstrated that LysoFix-GBA is selectively cleaved by GCase.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21] Cell permeable fluorogenic substrates for in situ measurement of GCase activity in cultured cells have recently been developed. 22,23 Other recent tools to detect active GCase molecules in situ are fluorescent cyclophellitol-based activity-based probes (ABPs). 24,25 These cell permeable probes selectively react with GCase by covalent and irreversible binding to its catalytic nucleophile, E340.…”
Section: Introductionmentioning
confidence: 99%
“…Onset of GD disease can be sensitively detected by demonstration of elevated plasma protein markers of Gaucher cells, like chitotriosidase, C–C motif chemokine ligand 18, and glycoprotein nonmetastatic melanoma protein B, as well as elevated plasma glucosylsphingosine 19–21 . Cell permeable fluorogenic substrates for in situ measurement of GCase activity in cultured cells have recently been developed 22,23 . Other recent tools to detect active GCase molecules in situ are fluorescent cyclophellitol‐based activity‐based probes (ABPs) 24,25 .…”
Section: Introductionmentioning
confidence: 99%